Specimen representation on the prediction of artificial test lightning plasma, resulting specimen loading and subsequent composite material damage. (1st January 2020) - Millen, S.L.J.; Murphy, A.; Abdelal, G.; Catalanotti, G.
Abstract: Preceding work has established that artificial test lightning plasma and composite test specimen damage can be modelled. However, no work has studied the impact of specimen representation in the modelling of the plasma and the resulting impact on specimen composite damage. Herein four distinct specimen designs have been modelled, with a magnetohydrodynamic FE multiphysics model employed to simulate the plasma and a FE thermal-electric modelling approach used to predict composite material damage. For the test arrangements modelled herein it has been found that specimen representation has limited impact on plasma global structure, even with significant change in specimen properties (e.g. from copper to epoxy). However, noteworthy variation in the local specimen surface loading is witnessed with specimen property change (e.g. epoxy to carbon reinforced epoxy), with peak magnitudes for surface pressure, velocity, current density and temperature changing by up to 88%. Such variation in local specimen surface loading does significantly vary the prediction of composite material thermal damage depth (up to 1200%) and surface damage area (up to 1314%). Moreover, this work, for the first time, provides predictions for the thermal damage suffered by both protected and unprotected composite specimens exposed to test standard Waveform B.